Multi-angle swirling fluidized bed drying of stingless bees pot-pollen - Luqman, Abdul Halim; Mohamad Firdaus, Basrawi; Ahmmad Shukrie, Md Yudin; Nurul Aini, Razali; Ahmad Syazwan, Ramli (IOP Publishing, 2024)
Pot-pollen is another stingless bee product, a mixture of pollen, honey, and bee enzyme stored in cerumen pots. Pot-pollen is protein rich and have therapeutic properties. However, they contain high moisture rendering them susceptible to microbial and fungi growth which will lead to spoilage without proper storage. Conventional methods to remove moisture includes sun drying, oven drying, and food dehydrators. However, they can be unhygienic, reduce pot-pollen quality, and lengthy drying time. Swirling fluidized bed dryer (SFBD) is a promising alternative as they have rapid drying time without damaging the nutrients. The addition of multi-angle swirling distributor (MASD) has the potential to improve drying performance without additional energy input. The current study aim to investigate the drying performance of swirling fluidized bed dryer with multi-angle distributor. Raw pot-pollen is dried in a lab scale SFBD at 3.0 m/s using single angle and multi-angle swirling distributors, 6767, 6730, and 6745. The results shown that the multi-angle swirling distributors 6730 and 6745 improved the drying performance of SFBD, by 17.1 % and 6.5 %, respectively. The best drying performance is shown by the 6730 distributor. Thus, multi-angle SFBD is able to rapidly dry the heat-sensitive stingless bee pot-pollen and represented significant improvement from single angle SFBD.